In vitro Antioxidant and In vivo Analgesic Activities of Citrullus lanatus Rind and Flesh Extract: A Comparison (Bangladesh Pharmaceutical Journal, 2022)
The present study was carried out to assess and compare the analgesic and antioxidant potential of Citrullus lanatus rind and flesh extract. The methanolic extract of the rind and ethyl acetate extract of the flesh were evaluated for their in vivo analgesic activity through the acetic acid-induced writhing method on Swiss Albino mice. The free radical scavenging activity of the extracts was measured by total phenolic content measurement and the DPPH method. The flesh extract showed higher antioxidant activity than the rind extract in both methods. In case of the evaluation of analgesic activity, the results were obtained in a dose dependent manner. At 200 and 400 mg/kg doses, both extracts displayed moderate analgesic property in a statistically significant manner (p < 0.05) with respect to aceclofenac sodium. The flesh extract was found to provide a better effect than the rind extract in this case as well. It may be concluded that the ethyl acetate extract of C. lanatus flesh and the methanolic extract of the rind possessed potential antioxidant and analgesic activities and might be used as sources of nutraceuticals or functional foods.Bangladesh Pharmaceutical Journal 25(1): 67-72, 2022 (January)